2005
DOI: 10.1038/nature04007
|View full text |Cite
|
Sign up to set email alerts
|

Mammal-like muscles power swimming in a cold-water shark

Abstract: Effects of temperature on muscle contraction and powering movement are profound, outwardly obvious, and of great consequence to survival. To cope with the effects of environmental temperature fluctuations, endothermic birds and mammals maintain a relatively warm and constant body temperature, whereas most fishes and other vertebrates are ectothermic and conform to their thermal niche, compromising performance at colder temperatures. However, within the fishes the tunas and lamnid sharks deviate from the ectoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 18 publications
2
57
0
Order By: Relevance
“…We suggest that this advantage, coupled with the previously recognized benefit of thermal niche expansion, could outweigh high energetic costs incurred by RM endothermy and, thus, has facilitated the radiation and diversification of tunas and endothermic sharks. Our analyses also indicate that fishes with RM endothermy are similar to birds and mammals in many respects, including not only high metabolic rates (2) and temperature dependence of muscle function (37), but also fast cruising speeds and the capabilities of large-scale migrations.…”
Section: Resultsmentioning
confidence: 53%
“…We suggest that this advantage, coupled with the previously recognized benefit of thermal niche expansion, could outweigh high energetic costs incurred by RM endothermy and, thus, has facilitated the radiation and diversification of tunas and endothermic sharks. Our analyses also indicate that fishes with RM endothermy are similar to birds and mammals in many respects, including not only high metabolic rates (2) and temperature dependence of muscle function (37), but also fast cruising speeds and the capabilities of large-scale migrations.…”
Section: Resultsmentioning
confidence: 53%
“…All 3 species have been documented feeding within Alaskan waters and the Bering Sea (Compagno, 1984;Benz et al, 2004;Martin, 2005). However, lamnid sharks, including the salmon shark (Smith and Rhodes, 1983;Anderson and Goldman, 2001;Goldman et al, 2004;Bernal et al, 2005) and the white shark (McCosker, 1987;Goldman, 1997), have been shown to maintain body-core and stomach temperatures consistently 6-15°C above ambient temperatures even in subarctic regions with SSTs below 5°C. Therefore, the Pacific sleeper shark emerges as the only potential predator of Steller sea lions in the North Pacific and Bering Sea region whose body-core temperatures likely remain at mid-water values.…”
Section: Discussionmentioning
confidence: 99%
“…Optimum frequency and power output of yellowfin tuna slow-twitch muscle are temperature dependent (Altringham and Block, 1997) and slowtwitch muscle from the endothermic salmon shark is unable to produce positive work at low temperatures (Bernal et al, 2005), raising the possibility that bluefin tuna slow-twitch muscle would be similarly impaired at cold temperatures. The decline in optimum contraction frequency at low temperature in vitro indicates that cold muscle should be least effective at high swimming speeds (Altringham and Block, 1997).…”
Section: Discussionmentioning
confidence: 99%